Protective Effects of Roselle Aqueous Extracts against UV-Induced Damage in Zebrafish Fins - I-Ting Lee; Ching-Yuan Huang; Wei-Lin Su; Tran M. Truong; Chi-Chung Wen; Bo-Chang Wang; Yau-Hung Chen (Fishes, 2024)
(1) Background: Roselle (Hibiscus sabdariffa) is a flowering plant reported to have anti-obesity, antioxidant, antibacterial, and anti-inflammatory effects. This study aims to evaluate the UV-absorbing and antioxidant activities of roselle aqueous extracts (RAE) and test the protective effects of RAE against UV radiation in zebrafish embryos. (2) Methods: DPPH assay and UV-spectrum methods were applied to evaluate the antioxidant and UV-absorbing activities, respectively. The protective effects of RAE were evaluated using fin morphology recording, Kaplan–Meier analysis, and Cox proportional hazards regression. Real-time PCR experiments were also applied to detect both the UV- and RAE-induced gene expressions. (3) Results: Our results show that (i) RAE had UV-absorbing abilities and significantly reduced ROS production in vitro; (ii) the mean times of malformed fins in the UV + RAE (36 and 48 ppm) groups were 3.56 and 4.44 days, respectively, and were prolonged compared to those in the UV-only group (3.36 days); (iii) zebrafish in the UV + RAE (36 and 48 ppm) groups were 0.963 and 0.496 (p < 0.001) times more likely to develop to malformed fins, respectively, than those in the UV-only group; and (iv) the RAE treatment led to the 0.19- to 0.62-fold downregulation of the p53, p21, mdm2, and bcl2 gene expressions, compared to the UV-only group. (4) Conclusions: The UV-protective effects of RAE might derive from both the in vitro UV-absorbing activity and in vivo regulation of the p53, p21, mdm2, and bcl2 gene expressions.